A Tripartite Interaction among the Basidiomycete Rhodotorula mucilaginosa, N2-Fixing Endobacteria, and Rice Improves Plant Nitrogen Nutrition. Issue 2 (22nd November 2019) - Paul, Karnelia; Saha, Chinmay; Nag, Mayurakshi; Mandal, Drishti; Naiya, Haraprasad; Sen, Diya; Mitra, Souvik; Kumar, Mohit; Bose, Dipayan; Mukherjee, Gairik; Naskar, Nabanita; Lahiri, Susanta; et al.
Abstract : An interkingdom interaction between the endophytic red yeast Rhodotorula mucilaginosa and diazotrophic endobacteria improves N nutrition in rice. Abstract: Nitrogen (N) limits crop yield, and improvement of N nutrition remains a key goal for crop research; one approach to improve N nutrition is identifying plant-interacting, N2 -fixing microbes. Rhodotorula mucilaginosa JGTA-S1 is a basidiomycetous yeast endophyte of narrowleaf cattail ( Typha angustifolia ). JGTA-S1 could not convert nitrate or nitrite to ammonium but harbors diazotrophic (N2 -fixing) endobacteria ( Pseudomonas stutzeri ) that allow JGTA-S1 to fix N2 and grow in a N-free environment; moreover, P. stutzeri dinitrogen reductase was transcribed in JGTA-S1 even under adequate N. Endobacteria-deficient JGTA-S1 had reduced fitness, which was restored by reintroducing P. stutzeri . JGTA-S1 colonizes rice ( Oryza sativa ), significantly improving its growth, N content, and relative N-use efficiency. Endofungal P. stutzeri plays a significant role in increasing the biomass and ammonium content of rice treated with JGTA-S1; also, JGTA-S1 has better N2 -fixing ability than free-living P. stutzeri and provides fixed N to the plant. Genes involved in N metabolism, N transporters, and NODULE INCEPTION -like transcription factors were upregulated in rice roots within 24 h of JGTA-S1 treatment. In association with rice, JGTA-S1 has a filamentous phase and P. stutzeri only penetrated filamentous JGTA-S1. Together, these results demonstrate an interkingdom interaction that improves rice N nutrition.